Description of the Correct Hand Washing Knowledge in School-Age Children in Elementary School: Gambaran Pengetahuan Cuci Tangan Yang Benar Pada Anak Usia Sekolah Di Mts - Delvia Pramiswari Raditia; Yanik Purwanti (Academia Open, 2022)
Washing hands is an act of sanitation by cleaning hands and between fingers using running water and soap by the community to be clean and break the chain of germs. The design of this study was carried out descriptively without statistical testing with a population of 37 students at Mts Nahdlatul Ulama', Candi Sidoarjo sub-district. This study used primary data by filling out closed questionnaires. Based on the results of the study, almost all 30 students (82%) had good knowledge and a small portion of students 7 (18%) had sufficient knowledge. The conclusion of the study is that there is still a lack of knowledge of proper hand washing in school-age children.